Restructure, repurpose, extend. Design strategies for future-oriented building and for strengthening the potential of the existing building fabric. Issue 1 (1st September 2022) - Herrmann, F; Pürschel, H; Wörner, J; Blasius, J; Lahiri, L; Böhme, M; Hartmann, V
Abstract: Climate neutrality coupled with an overall positive ecological footprint is still a distant dream for new construction. The German building sector is directly and indirectly responsible for about 40% of all German CO 2 emissions and has so far failed its CO 2 reduction goals. For the German building sector, the key to climate neutrality lies not only within new construction but in its existing building fabric. The embodied carbon of new construction needs be reduced as well as the amount of new construction itself. Hence the reuse of buildings and the extension of their life cycles is a crucial factor in reducing CO 2 emissions and resource consumption. In this paper we present three of our projects (from the office Sauerbruch Hutton), highlighting not only the potentials but also the problems that planners face with existing buildings. Additionally, our project based LCA analysis showcases that retrofitting can have a much smaller CO 2 footprint than a new building.